Commitment to Exercise: The Influence of Personal, Athletic, and Psychological Characteristics - Gomes, Rui; Universidade do Minho Escola de Psicologia Campus de Gualtar 4710-057-Braga Portugal (2012)
This study analyzes the influence of personal, psychological and athletic characteristics of participants regarding the commitment to exercise practice. The study included 153 participants divided in the adherer group (N = 102) and the dropout group (N = 51). Personal and athletic information, exercise attitudes, perceived behavioral control, intended exercise frequency, goal orientations, behavioral regulation, and expected exercising outcomes were evaluated. The results showed that the participants in the adherer group expressed a greater desire to maintain or increase their weight, they had more experience exercising, had greater intrinsic regulation, and assumed more positive and fewer negative exercise expectations. In conclusion, considering the role of personal, athletic, and psychological characteristics seems important in order to prevent abandoning exercise altogether.